Four Works on Women in Islam - Mazen Hashem (International Institute of Islamic Thought, 1993)
This book is a penetrating study of several of the Qur'anic verses and hadiths used to construct and justify a "skewed" understanding of femininity: "He created you from a single soul, and then He created from it/like-nature its mate" (4:1); " ... mighty is your snare" (12:27); "Fair in the eyes of men/people is the love of things they covet: women and sons ..." (3:14); the concept of shahawiit (earthly desires); and the hadith "she was created from a rib." The discussion is based on a close reading of several tafasir. One notices immediately that many of these sources dignify women and do not advocate the conventional view prevaling in contemporary Muslim societies. The book makes no apology to any author or source that presents a stereotypical view of women; instead, it criticizes their methodology on the ground that they followed the traditions of the Bible and the Jews. In the second section, the discussion departs from a direct analysis of texts to elaborate on an Islamic typology of modem Muslim women. The author, now writing as an activist, no longer argues with others, but is concerned with getting his own understanding across. Therefore he is not concerned with nonnative understanding, but rather seeks the best Islamic judgment, within the context of present circumstances and world culture, on this issue. The book is totally progressive, straight to the point, and does not make compromises to please traditionalists. Al Mar'ah bayna Ta'lim al Din wa Taqalid al Mujtama' By Hasan al Turabi: Jeddah: al Dar al Sa'udiyah li al Nashr wa Tawzi, 1984 ...